2010
DOI: 10.1186/1297-9686-42-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of two myostatin (MSTN) mutations on weight gain and lamb carcass classification in Norwegian White Sheep (Ovis aries)

Abstract: BackgroundOur aim was to estimate the effect of two myostatin (MSTN) mutations in Norwegian White Sheep, one of which is close to fixation in the Texel breed.MethodsThe impact of two known MSTN mutations was examined in a field experiment with Norwegian White Sheep. The joint effect of the two MSTN mutations on live weight gain and weaning weight was studied on 644 lambs. Carcass weight gain from birth to slaughter, carcass weight, carcass conformation and carcass fat classes were calculated in a subset of 508… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 8 publications
1
53
1
1
Order By: Relevance
“…Myostatin (MSTN), also known as growth differentiation factor 8 (GDF-8), is an important negative regulator in skeletal muscle development. Inactivation of the MSTN gene in mice (Mendias et al, 2008) or mutations in bovine (McPherron and Lee, 1997), sheep (Boman et al, 2010), and humans (Schuelke et al, 2004) result in a similar phenotype of increased muscle growth. Therefore, these three genes, MRF4, MSTN, and MyoG, are always used as indicators of skeletal development.…”
Section: Discussionmentioning
confidence: 99%
“…Myostatin (MSTN), also known as growth differentiation factor 8 (GDF-8), is an important negative regulator in skeletal muscle development. Inactivation of the MSTN gene in mice (Mendias et al, 2008) or mutations in bovine (McPherron and Lee, 1997), sheep (Boman et al, 2010), and humans (Schuelke et al, 2004) result in a similar phenotype of increased muscle growth. Therefore, these three genes, MRF4, MSTN, and MyoG, are always used as indicators of skeletal development.…”
Section: Discussionmentioning
confidence: 99%
“…Boman et al (2009) reported a c.960delG mutation in the MSTN gene in Norwegian White sheep that causes a more pronounced phenotype regarding meat and fat measurements, as compared to the g.+6223G>A (c.2360G>A) mutation. This is evident since it is expected that no functional protein is produced in c.960delG homozygotes (Boman et al 2009(Boman et al , 2010. In contrast, in g.+6223G>A animals, the GDF8 protein is reduced to about one third and thus not completely abolished (Clop et al 2006).…”
Section: A Mutation In the Myostatin Gene Causes A Hypermuscled Phenomentioning
confidence: 86%
“…Additional SNPs (g-41C˃A, g+ 4036A˃C and g+ 6223G˃A) have been identified in the promoter and intron 2 regions and showed significant effects on slaughter measurements of muscling and fatness (Kijas et al, 2007). Another two SNPs (C.2360G˃A and C.960delG) have been detected and are reported to reduce fatness and increase muscle mass in Norwegian White sheep (Boman et al, 2010). A single strand conformational polymorphism analysis (SSCP) of the 473-bp of the exon 1-intron 1 region of myostatin gene has revealed three allelic variants in NZ Romney sheep (Zhou et al, 2008).…”
Section: Gene Marker Laboratory Agriculture and Life Sciences Divisimentioning
confidence: 98%
“…These results are partially consistent with the observations made by who found that the myostatin genotypes in intron 1 significantly affected leg yield, loin yield, total yield and loin yield% and tended to affect shoulder%. Boman et al (2010) detected two myostatin mutation (c.2360G>A and c.960delG) in the Norwegian White Sheep. Both mutations affected conformation and fat class that caused yielding carcasses with less fat and increased muscle mass.…”
Section: Effect Of Myostatin Genotype On Carcass Traitsmentioning
confidence: 99%